PENGENDALIAN PERSEDIAAN KAIN KATUN DRILL MENGGUNAKAN METODE EOQ (ECONOMIC ORDER QUANTITY) PADA CV SINAR RAHAYU - Sobari, Rapid Hadi; Supriyadi, Supriyadi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This research was conducted at CV Sinar Rahayu, a company engaged in manufacturing hats. Based on the observation results, problems were found in the inventory section, where CV Sinar Rahayu did not use storage space effectively so that the company often ran out of raw material stock. The increasing frequency of material purchases leads to high raw material ordering costs. The purpose of this study is to analyze the inventory management of cotton drill raw materials at CV Sinar Rahayu and apply the EOQ (Economic Order Quantity) method to minimize the cost of raw material inventory of cotton drill fabrics. Due to unstable inventory costs and frequent inventory shortages, the author uses the EOQ (Economic Order Quantity) method to be able to minimize the cost of inventory of raw materials for cotton drill fabric. The method used in this study is a descriptive quantitative method using primary data analysis with a data collection process by direct observation at the research site. The results obtained that if the EOQ (Economic Order Quantity) method is applied at CV Sinar Rahayu, it can minimize the total amount of inventory costs by 56.03%. In addition, other costs will decrease, one of which is the ordering fee without any additional storage fees. With the results obtained, it can be concluded that the EOQ (Economic Order Quantity) method is a method that can optimize the control of the supply of raw materials for cotton drill fabrics at CV Sinar Rahayu company so that it can minimize the cost of raw material inventory.